Urban air pollution: comparative study. (2015) - Bhave, Prashant P.; Kulkarni, Nikhil Shirish
The air pollution status in one of the metropolitan city from India, Mumbai was compared with the predicted results using US-EPA regulatory dispersion model - AERMOD on the basis of emission loads given by CPCB and NEERI. The present air-pollution status at two monitoring locations 'Sion' from central Mumbai and 'Bandra' from western Mumbai were compared for concentrations of two air pollutants namely PM10 and NOx for the year 2012. The results obtained for the monitoring locations at 'Sion' and 'Bandra' shows that the present observed concentrations of PM10 are more than the predicted concentrations. However, in case of NOx, the observed concentrations were found to be less than the predicted concentrations at Sion and Bandra. Comparison of the results of the study indicate that the development activities, plans and policies to control air pollution in the city have controlled the rate of increase in NOx but failed to control the rate of increase in PM10 . This paper will provide another direction to the researchers and decision makers/planners to focus on the effectiveness of the implemented plans and policies with the help of air pollution modelling.